If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(0) + 9y = -18 Multiply -5 * 0 0 + 9y = -18 Anything times zero is zero. 0 + 9y = -18 Remove the zero: 9y = -18 Solving 9y = -18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '9'. y = -2 Simplifying y = -2
| r-(-1)=9 | | 9(3n+3)=7(2n+4)+6 | | 6(x+8)-x=5x+4 | | -2(t-5)+4t=9t-6 | | 2x-9=2x-45 | | x(x+5)=(2x+10)(x-2) | | 5y-5+11x-1=9x+21 | | 15n-5=n+325 | | X^2+x=2y | | 9-(6y+2x)=8(x-y) | | 1+.80z=2+.75z | | 9*1+3=y | | 3y=32+5y | | 7w-11-4w=6 | | 12(x+8)-x=5x+4 | | M+3m+9m-4= | | 6(2n+3)=8(9n+6)+8 | | 3l+9-l-6= | | 4+.14x=5 | | 9y+3=3y+9 | | 4k-9=-3(k+7) | | 12r-(r-7)+6=3(r+6)+8r | | x+3x-2x-2=13 | | 9y+9=3y+9 | | 3k^2=10k-3 | | 8x+5=35+5x | | 42=6x+4-x+13 | | 3t+5=3*5+t | | 10-6p+5p-4= | | 5+2(n+1)=2h | | -4(2t-t)+5t=4t-2 | | 3(5x-7)-12x=-9 |